Early versus late endoscopic treatment of pancreatic necrotic collections: A systematic review and meta-analysis - Kamal, Faisal; Khan, Muhammad Ali; Lee-Smith, Wade M.; Sharma, Sachit; Acharya, Ashu; Faggen, Alec E; Farooq, Umer; Tarar, Zahid I; Aziz, Muhammad; Baron, Todd (Endoscopy International Open, 2023)
Background and study aims Recently studies have compared early (<4 weeks) vs. late or standard (>4 weeks) endoscopic treatment of pancreatic necrotic collections (PNC) and have reported favorable results for early treatment. In this meta-analysis, we compared the efficacy and safety of early vs. late endoscopic treatment of PNC.Patients and methods We reviewed several databases from inception to September 30, 2021 to identify studies that compared early with late endoscopic treatment of PNC. Our outcomes of interest were adverse events (AEs), resolution of PNC, performance of direct endoscopic necrosectomy, need for further interventions, and mean number of endoscopic necrosectomy sessions. We calculated pooled risk ratios (RRs) with 95% confidence intervals (CIs) for categorical variables and mean differences (MDs) with 95% CIs for continuous variables. Data were analyzed by random effect model. Heterogeneity was assessed by I2 statistic.Results We included four studies with 427 patients. We found no significant difference in rates of AEs, RR (95% CI) 1.70 (range, 0.56–5.20), resolution of necrotic or fluid collections, RR (95% CI) 0.89 (range, 0.71–1.11), need for further interventions, RR (95% CI) 1.47 (range, 0.70–3.08), direct necrosectomy, RR (95% CI) 1.39 (range, 0.22–8.80), mortality, RR (95% CI) 2.37 (range, 0.26–21.72) and mean number of endoscopic necrosectomy sessions, MD (95% CI) 1.58 (range,–0.20–3.36) between groups.Conclusions Early endoscopic treatment of PNC can be considered for indications such as infected necrosis or sterile necrosis with symptoms or complications; however, future large multicenter studies are required to further evaluate its safety.
Keywords: Endoscopic ultrasonography; Pancreas; Intervention EUS